Development and validation of a questionnaire to assess the implementation of physical education programs in Chinese junior high schools - He, Liu; Mohd Ayub, Ahmad Fauzi; Amri, Saidon (BioMed Central, 2024)
Background: Students’ physical fitness has always been the focus of attention of the Chinese government, and the school as an important way to improve students’ physical fitness, there are many studies on the current status of the implementation of physical education in schools, and there are many studies that use self-made questionnaires to investigate the implementation of physical education in schools, but most of the studies do not adequately validate the self-made questionnaires, so the purpose of this study was to develop a questionnaire to assess the level of implementation of physical education programmes in Chinese junior secondary schools and to test its reliability and validity. Method: The content of the questionnaire was developed based on the content of Annex 1 of the Assessment Measures for Physical Education in Primary and Secondary Schools issued by the Ministry of Education of China in 2014 and was modified based on feedback from the expert panel and pre-test participants. The questionnaire was initially tested for validity by 5 expert reviewers, and then we collected data information from 350 participants and conducted exploratory factor analysis (EFA) to explore the factor structure of the initial version. One week later, 40 of the 350 participants were randomly selected to assess test-retest reliability. Results: The I-CVI and KAPPA value analysis results of the expert review results show that the questionnaire has extremely high reliability and consistency among experts. EFA results indicate that the five dimensions of this questionnaire are highly reliable. In the test-retest reliability, the Pearson correlation coefficients of the initial test data and the retest data of each dimension are all greater than 0.7, and the significance probability values are all less than 0.05, reaching the significance level, the results show that the questionnaire has good stability. Conclusions: This study concluded that the 5 dimensions and 38 items of this questionnaire had high reliability and validity and could be used as a preliminary tool to measure the implementation level of physical education programs in junior high schools in China. However, future research should explore the potential need for adjustment to suit different regions and cultures.